Improving RFID read rate reliability by a systemic error detection approach - Potdar, Vidyasagar; Chang, Elizabeth; Hayati, P. (Institute of Electrical and Electronics Engineers (IEEE), 2007)
Reliability, security and privacy are the key concerns with RFID (radio frequency identification) adoption. While the mainstream RFID research is focused on solving the security and privacy issues, this paper focuses on addressing the reliability issues in general and detecting read rate failures in particular. We specifically consider the issue of detecting if some RFID tags are not read at all, and if the tags are not read an alarm should be activated. This is quite different from the main stream RFID reliability research which attempts to increase the read rate by developing new and powerful antennas or improving the surrounding environment. To address this issue, we present a novel solution which can detect missed readings and notify appropriate entity to take suitable action against it. The novelty of the proposed solution lies in the combined use of RFID reader along with a normal weighing machine. The concept is to compare the gross weight of the tagged items against the gross weight (of the same items) stored in a backend database. The backed database can only be accessed for those RFID tags which are properly read. If some tags are not read at all these weights would vary and hence incorrect readings could be identified. This paper provides the detailed theoretical foundation for the proposed solution. In addition we compare the proposed solution against existing solutions to demonstrate the success and potential of our solution for practical deployment of RFID in library or supermarket scenario.